Development of bone-mimicking resin for 3D printing with enhanced mechanical properties using ceramic filler - Wei-Chun Lin; Chia-Cheng Cheng; Jui-Fu Tang; Kuan-Chung Huang; Kevin Chiou; Ying-Ruei Liu; Yu-An Chen; Zhi-Xian Wu; Yu-Hsien Chu; Yu-Chun Huang; Wei-Chih Chen (Polymer Testing)
In recent years, rapid advancements have been made in the field of additive manufacturing, which is also called three-dimensional (3D) printing. Liquid crystal display (LCD) photo-curing 3D printing is highly regarded for its exceptional printing speed and accuracy. These benefits have been extensively employed in medical applications. After obtaining a 3D model file through medical image scanning techniques, including computed tomography and magnetic resonance imaging, it is easy to produce a realistic model with an LCD 3D printer. Furthermore, 3D-printed models can observe the region of interest and facilitate surgical simulation training. However, existing 3D printing materials are inadequate for simulating real bone. The aims of this study are to enhance the mechanical properties of photocured resins with different ceramic powders and to mimic the complexity of the bone structure. Two ceramic particles—aluminum oxide and calcium carbonate—are mixed with the photosensitive resin before polymerization. In addition, appropriate dispersants are used to ensure proper dispersion of the powder in the resin. The rheological properties and mechanical properties of the composite resins are investigated. In this research, the mechanical properties of a newly synthesized composite polymer are significantly improved, with comparable characteristics to those of real bones.